2016
DOI: 10.1111/gfs.12239
|View full text |Cite
|
Sign up to set email alerts
|

Soil water dynamics and dry‐matter production of old man saltbush‐, native grass‐ and lucerne‐based pastures in a variable summer‐dominant rainfall environment, Australia

Abstract: In a summer‐dominant high‐rainfall, yet seasonally dry environment, soil water dynamics and dry‐matter (DM) production were monitored during 2006–12, for three perennial pasture types: old man saltbush (Atriplex nummularia ssp. nummularia with native grass), native grass (Bothriochloa macra and Rytidosperma bipartita dominant) and lucerne (Medicago sativa cv. Venus). Plant root depth of the old man saltbush pasture (1·5 m) was greater than that of native grass (1·2 m), but equal to that of lucerne (1·5 m), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 26 publications
(46 reference statements)
2
9
0
6
Order By: Relevance
“…Preliminary findings for this study were previously reported for plant root depth (Murphy et al., 2008a), water use efficiency (Murphy et al., 2008b) and soil water dynamics of tropical grasses (Murphy, Lodge, Brennan et al., ) and saltbush‐based pastures (Murphy et al., ).…”
Section: Methodssupporting
confidence: 79%
See 4 more Smart Citations
“…Preliminary findings for this study were previously reported for plant root depth (Murphy et al., 2008a), water use efficiency (Murphy et al., 2008b) and soil water dynamics of tropical grasses (Murphy, Lodge, Brennan et al., ) and saltbush‐based pastures (Murphy et al., ).…”
Section: Methodssupporting
confidence: 79%
“…The climate of the region is typical of moist mid‐latitudes having a mild winter and hot humid summer (Köppen‐Geiger class Cfa—humid subtropical, Peel, Finlayson, & McMahon, ). Site characterization including exploratory soil coring, soil profile physical and chemical characteristics and establishment of treatments was reported by Murphy, Boschma, and Harden (). Briefly, soil surface texture was a silty loam and the B‐horizon at 0.3 m was silty clay loam–silty light clay with a mean maximum depth of 1.61 m. Bulk density increased with depth of soil with values ranging from 1.29 at the surface to 1.87 Mg/m 3 at 1.3–1.5 m, and bulk density was always <1.6 Mg/m 3 for soil layers shallower than 0.9 m. The plant available water capacity (PAWC), being the difference between profile SSW at drained upper limit (c. –10 kPa, 567 ± 26 mm) and crop lower limit (c. –1,500 kPa, 306 ± 29 mm) was 261 ± 3 mm (McKenzie & Cresswell, ; Murphy et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations